Minimizing chemotherapy-induced peripheral neuropathy: preclinical and clinical development of new perspectives. (August 2015) - Poupon, Laura; Kerckhove, Nicolas; Vein, Julie; Lamoine, Sylvain; Authier, Nicolas; Busserolles, Jérôme; Balayssac, David
Abstract : Introduction: Chemotherapy-induced peripheral neuropathies (CIPN) are a dose-limiting adverse effect of certain anticancer drugs (platinum salts, vinca alkaloids, taxanes, bortezomib, thalidomide, epothilones, eribulin). CIPN are mainly responsible for sensory disturbances and are associated with a decrease in quality of life. After the end of chemotherapy, CIPN can last for several months and even years. Unfortunately, recent meta-analyses of clinical trials have demonstrated that there is no univocal gold standard for the prevention and treatment of CIPN. Areas covered: Using animal models of CIPN, several new strategies to prevent or treat CIPN are under development. These new strategies involve several pathways, including ion channels, neuroprotectants, glutamatergic neurotransmission, oxidative stress, cannabinoid system, inflammation, and mitochondrial functions. Expert opinion: To date, based on meta-analyses of clinical trials, no drug can be proposed as a gold standard to prevent or treat CIPN. Consequently, there is a strong discrepancy between the optimistic results of animal studies and the poor outcomes of clinical trials. Pain assessment in preclinical and clinical studies is probably not the best outcome measurement tool and all these studies should include composite outcomes including the full complexity of CIPN symptoms, such as positive symptoms (pain, paresthesia, and dysesthesia) and negative ones (numbness).